Management if marine debris from ships in compliance to MARPOL 73/78 Annex V - Julyus, Melvin Mobilik (Universiti Malaysia Sarawak(UNIMAS), 2016)
Marine debris is widely distributed at the ocean surface and coastal area, but their specific sources, quantities and distribution remain uncertain. Although, studies have been conducted to estimate the quantity of debris along the Malaysian beaches, marine sources especially from the shipborne garbage was not extensive. In addition, the large number of vessels using Malacca Straits as an important trading route may produce pressure on the marine environment, particularly garbage accumulated on the vessels navigating within Malaysian Territorial Water. Therefore, this study was designed to investigate marine debris abundance in Malaysia marine environment from shipborne garbage source. This study adopted a standard method of beach marine debris survey and shipborne garbage survey to assess the types, amount, categories and sources of debris on eight public beaches and five ports in Malaysia. Beach marine debris study was conducted during the northeast monsoon (NEM), southwest monsoon (SWM) and intermediate monsoon (IM) seasons at Pandan, Pasir Pandak, Temasyah, Tg. Lobang, Tg. Aru, Kosuhoi, Saujana and Batu Rakit beaches. A total of 46,141 items (961 item/km) weighing 2,120 kg (44.2 kg/km) were collected and categorized during six surveys conducted at the beaches between October 2012 and August 2014. Debris accumulation was more abundant during SWM, while, plastic category (88.48%) dominating debris items collected at this study. Debris abundance stranded on the beaches can be attributed to urban proximity. As for shipborne garbage survey, 115 vessels were selected at Kuching (25 vessels), Bintulu (20 vessels), Kota Kinabalu (20 vessels), Sandakan (14 vessels) and Klang (36 vessels) ports en route through Malacca Straits. A total of 20,895 items (182 item/vessel) weighing at 6,316.1 kg (54.9 kg/vessel) were collected and categorized during surveys conducted on the vessels between October 2012 and October 2014. Sandakan port accumulated the highest mean shipborne garbage item (SGI) at 197 item/vessel, whereas, Kota Kinabalu port accumulated the highest mean shipborne garbage weight (SGW) at 64.0 kg/vessel. Shipborne garbage abundance is influenced by number of crews and vessels’ gross tonnage. As for shipborne garbage accumulation according to ship type, bulk carrier vessels accumulated the highest mean SGI (212 item/vessel) and SGW (63.8 kg/vessel). The low percentage of vessels equipped with garbage processing equipment (33.33%), may resulting the high percentage of plastic category (63.75%) ending in the marine environment. Although, many factors contributed to the marine debris abundance, human-generated debris was found to be the major source of the marine debris problem in this study. The presence of debris items associated with shipping activities found on the beaches indicated not all vessels comply with the new revised Annex V of the MARPOL 73/78. Therefore, promulgating awareness and educate the general public on pathway of marine debris needs to be collaborated with public participation to instill consciousness through environmental education. In addition, comprehensive and long-term monitoring along Malaysian coastline is paramount to identifying marine debris point source. Thus, specifying and implementing strategic solution besides determining priorities to ensure total eradication of illegal discharge at sea and understanding marine debris abundance relationship against dynamic climate conditions. This effort may be small but the impact as a result of this action will reduce the amount waste dispose of at sea tremendously.